The Causality of the First Unmoved Mover in Confrontation: From E. Berti and K. Flannery to the Present - Serra Pérez, Manuel Alejandro (Acta Philosophica, 2023)
In the last two decades, one of the topics that has had the greatest repercussion in the study of the Corpus Aristotelicum has been undoubtedly the book Λ of the Metaphysica, more particularly that of the causality of the First Unmoved Mover. The element that has marked the turning point in the interest in this topic has its origin in the contributions that one of the current greatest specialists in Aristotle, the Veronese Enrico Berti, has been making, specially because they contrast with that which is known as a “traditional thesis”. So, faced with the Bertian challenge, another researcher of Aristotle, K. Flannery, objected to the reasons the Italian believed he could base his criticism of that position. The study of this confrontation, together with the academic works with which the specialists have been contributing on this subject to the present day, will give us the opportunity to offer some lines of research in order to better understand and assess this difficult, but fundamental matter.